Self-regulation from a process perspective - Perels, Franziska; Otto, Barbara; Landmann, Meike; Hertel, Silke; Schmitz, Bernhard (Zeitschrift für Psychologie, 2007)
The first aim of this study was to analyze self-regulation from a process perspective. Therefore, a process model of self-regulation (Schmitz & Wiese, 2006) was described, postulating state components of self-regulation in three learning phases. The relationships within the model were investigated by means of univariate and multivariate time-series analyses based on process data collected through learning diaries. The second aim was to evaluate an intervention study with 8th-grade students as an example for training evaluation based on process data. The whole sample consisted of 249 8th-grade students; for time-series analyses a subsample of 66 students was used. The results concerning the first research question support the conceptualization of the process model and underline the process character of self-regulation as well as the state conceptualization of the model. The training evaluation results show that specifying the results of standard evaluations by means of control group comparison with time-series methods is enriching.